Live-streaming TikTok: Strategi mahasiswa cerdas untuk meningkatkan pendapatan di era digitalisasi - Agistiani, Risma; Rahmadani, Anisa; Hutami, Azzahra Ghaida; Kamil, Muhamad Taufik; Achmad, Nur Shakila; Rozak, Rama Wijaya Abdul; Mulyani, Heni (Nur Science Institute, 2023)
The rapid development of the live streaming trend in the digital era has made the TikTok application a popular platform for young people. However, the increasing number of TikTok users makes competing with other well-known Live Streamers difficult. This research aims to find specific strategies and best practices for live-streaming TikTok that are effective for students to maximize the potential for additional income in the digital era. This study uses a qualitative approach to gathering information from semi-structured interviews and non-participant observation. The research participants are five students who have succeeded in live streaming TikTok, have at least three months of experience in live streaming TikTok, and have generated income from this platform. There are two options for earning additional income through TikTok live streaming. First, become a live host with consistent income, or second, live stream independently to market products with inconsistent income.